Han: An Intercultural Theological Anthropology? - Considine, Kevin P (Interreligious Studies and Intercultural Theology, 2023)
This article argues that han should be received as an intercultural anthropology into global theological discourse, provides insight into some of the nuances of this anthropology, and shows the benefits of a thorough engagement with han. It suggests han anthropology be received as “intercultural” as opposed to “cross-cultural” or “trans-cultural.” The article then provides a brief overview of the development of han as a local anthropology of the Korean people and then interprets han using the work of Hwa-Young Chong and the philosophy of Jae-Hoon Lee to focus on han’s various manifestations—original and secondary—as well as won-han, jeong-han, and especially hu-han. It explains han’s ambiguous relationality, its potential for negative and positive transformation of life and society, its evocation of woundedness beyond “trauma,” and its deep connection to religion and ritual. I conclude that han continues to offer a rich and under-utilized resource for articulating Christian soteriologies between global and local that prioritize the “sinned-against.”